2017
DOI: 10.1007/978-94-024-1079-2_22
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Taurine-Rich Cuttlefish (Sepia officinalis) Extract Against Hydrogen Peroxide-Induced Oxidative Stress in SH-SY5Y Cells

Abstract: Oxidative stress mediates the cell damage in several neurodegenerative diseases, some of which are Alzheimer's disease (AD), multiple sclerosis and Parkinson's disease (PD). In this study, we investigated whether the taurine-rich cuttlefish extract could exert a protective effect on damaged human neuroblastoma SH-SY5Y cells induced by hydrogen peroxide (HO). Our results revealed that pre-treatment with cuttlefish extract effectively increased the cell viability by protecting the cells from intracellular reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the current study, we also analysed the role of taurine (100 μM and 200 μM), a well-known antioxidant substance, in counteracting the H 2 O 2 -induced oxidative stress. In our experimental conditions, taurine reduced the mitochondrial •O 2 − production and the ratio of apoptotic chondrocytes in accordance with previous results [ 52 , 53 , 54 , 55 ]. Recent evidence demonstrated the increase of antiapoptotic Bcl-2 protein and the reduction of proapoptotic Bax protein expression induced by taurine, confirming our data [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we also analysed the role of taurine (100 μM and 200 μM), a well-known antioxidant substance, in counteracting the H 2 O 2 -induced oxidative stress. In our experimental conditions, taurine reduced the mitochondrial •O 2 − production and the ratio of apoptotic chondrocytes in accordance with previous results [ 52 , 53 , 54 , 55 ]. Recent evidence demonstrated the increase of antiapoptotic Bcl-2 protein and the reduction of proapoptotic Bax protein expression induced by taurine, confirming our data [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that L-citrulline supplementation increased the bioavailability of L-arginine and promoted NO synthesis [24]. Taurine is a semiessential amino acid in mammals and has been proven to have multiple bene cial effects, including attenuating in ammation-and endoplasmic reticulum stress-induced organ injuries [25][26]. Taurine treatment inhibited ethanolmediated cell apoptosis in the cerebellum [27].…”
Section: Discussionmentioning
confidence: 99%
“…Hosseinzadeh, A. et al reported that diallyl disulfide (DADS), which has antioxidant and anti-inflammatory properties, can increase nuclear transcription factor erythroid-2-like factor 2 (Nrf2) nuclear translocation, and the gene expression of antioxidant enzymes, and it reduced the IL-1β-induced elevation of ROS [ 62 ]. Kim, Y. S. et al revealed that taurine increased cell viability by protecting cells from ROS-induced by H 2 O 2 exposure [ 63 ]. In addition, Qiu, L. et al showed that LRWXG, a flavonol-type flavonoid ubiquitously present in vegetables, attenuated ROS generation and promote glutathione (GSH) and glutathione peroxidase (GSH-PX) expression levels in an OA rat [ 64 ].…”
Section: Mitochondrial Metabolism Dysfunction To Oa Pathogenesismentioning
confidence: 99%
“… Drugs Mechanism Function Ref. DADS Increase Nrf2 nuclear translocation and gene expressions of antioxidant enzymes Reduce the production of ROS [ 62 ] Taurine Scavenge excessive ROS Decrease the H 2 O 2 -induced ROS production [ 63 ] Quercetin Promote the expression of GSH and GSH-PX Attenuate the generation of ROS [ 64 ] AMPK/SIRT1 signaling pathway Inhibit cartilage ECM degradation Melatonin Inhibit H 2 O 2 cytotoxicity, iNOS, and COX-2 gene expression Reduce the oxidative stress and inflammatory responses [ 65 ] LRWXG Upregulate the expressions of Bcl-2 and downregulate the expressions of caspase-9, caspase-3, and Bax Inhibit the apoptosis of chondrocytes [ 66 ] CS Inhibit the expressions of caspase-3 and caspase-9 Inhibit the apoptosis of chondrocytes [ 67 ] Rg1 PI3K/Akt/mitochondrial signaling pathway Inhibit IL-1β-induced chondrocyte apoptosis [ 68 ...…”
Section: Mitochondrial Metabolism Dysfunction To Oa Pathogenesismentioning
confidence: 99%